Is Linear Advancement Related to Relapse in Unilateral Cleft Lip and Palate Orthognathic Surgery?. (November 2015) - Watts, Guy D.; Antonarakis, Gregory S.; Forrest, Christopher R.; Tompson, Bryan D.; Phillips, John H.
Objective: To investigate the stability of major versus minor Le Fort I maxillary advancements in unilateral cleft lip and palate (UCLP) patients. Design: A retrospective longitudinal study was undertaken on 30 nonsyndromic UCLP patients treated with the same protocol at The Hospital for Sick Children, Toronto, Canada. Patients were grouped into major and minor movement groups based on planned surgical advancement. Standard lateral cephalometric radiographs were taken preoperatively (T1), immediately postoperatively (T2), and at least 1 year postoperatively (T3). Skeletal and dental variables were measured using cephalometric analysis. Stability was compared between groups using repeated-measures analysis of variance. Linear regression analysis was used to assess the relationship between advancement and relapse for the entire study population. Results: A mean maxillary advancement of 9.8 mm and 4.9 mm was seen for the major (n = 10) and minor (n = 20) movement groups, respectively. The mean skeletal horizontal relapse was 1.8 mm (18%) for the major advancement group and 1.5 mm (31%) for the minor advancement group. There was no significant difference in skeletal horizontal relapse between the groups ( P > .05). The correlation coefficient ( r ) between linear horizontal advancement and relapse was calculated to be .31 ( P > .05). Dental horizontal relapse was not significant for either the major or minor groups, and no significant difference was found between the groups ( P > .05) Conclusion: Skeletal and dental relapse was found to be unrelated to the amount of maxillary linear advancement using conventional Le Fort I osteotomies in UCLP.